Seismic performance of historical vaulted adobe constructions: a numerical case study from Yazd, Iran - Sadeghi, Neda H. (2018)
Past earthquakes have demonstrated that historical vaulted adobe buildings are highly vulnerable to seismic actions. Hence, it is crucial for such building typologies to be evaluated in terms of seismic capacity. To this end, this article deals with the seismic performance of historical vaulted adobe houses from the city of Yazd, Iran as one of the seismically active areas of the world and possessing a very rich adobe heritage. Thus, and based on a detailed geometrical survey, a representative sample of adobe houses from Yazd was studied using a simplified in-plane analysis based on three geometric indexes. Concerning the out-of-plane behavior, a deeper assessment was conducted by performing a numerical study, where the main influential parameters on the seismic behavior of vaulted adobe buildings were considered. The numerical analyses were carried out by adopting the limit analysis theory implemented in the Block2D software. The results obtained indicate the safe in-plane behavior of most of the houses and the safe out-of-plane response of the sample under gravitational loads. However, the sample out-of-plane safety under earthquake-induced loads seems to be a matter of concern.